2017
DOI: 10.1038/s41467-017-00655-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of cytoplasmic inclusion bodies in cells infected by respiratory syncytial virus

Abstract: Infection of cells by respiratory syncytial virus induces the formation of cytoplasmic inclusion bodies (IBs) where all the components of the viral RNA polymerase complex are concentrated. However, the exact organization and function of these IBs remain unclear. In this study, we use conventional and super-resolution imaging to dissect the internal structure of IBs. We observe that newly synthetized viral mRNA and the viral transcription anti-terminator M2-1 concentrate in IB sub-compartments, which we term “I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
243
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(261 citation statements)
references
References 60 publications
(95 reference statements)
13
243
2
3
Order By: Relevance
“…In Mononegavirales, transcription and replication takes place in viral factories, e.g. cytoplasmic inclusions where the local concentration of viral proteins is increased thereby facilitating viral replication [53][54][55][56][57][58]. These viral factories, which can be either doublemembrane [59] or membrane-less organelles [60], also likely prevent the activation of host innate immunity by shielding viral proteins and thus impairing their interaction with cellular antiviral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In Mononegavirales, transcription and replication takes place in viral factories, e.g. cytoplasmic inclusions where the local concentration of viral proteins is increased thereby facilitating viral replication [53][54][55][56][57][58]. These viral factories, which can be either doublemembrane [59] or membrane-less organelles [60], also likely prevent the activation of host innate immunity by shielding viral proteins and thus impairing their interaction with cellular antiviral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…After fusion, the helical ribonucleoprotein complex (RNP) is released into the host cell cytoplasm. Transcription and replication occur in the cytoplasm in viral inclusion bodies that serve to concentrate viral products [165][166][167] . The viral RNA-dependent RNA polymerase (RdRp) complex is responsible for transcribing viral mRNA and synthesizing positive-sense anti-genome intermediates needed for replication of new negative-sense genomes for packaging into virions (reviewed elsewhere 168 ).…”
Section: Box 1 | the Life Cycle Of Respiratory Syncytial Virusmentioning
confidence: 99%
“…In our siRNA screen we showed that the nuclear RNA export factor 1 (NXF1) is necessary for the EBOV life cycle, and also for the life cycle of the highly pathogenic New World arenavirus Junín virus. These data suggest a mechanism of action that may be conserved among several cytoplasmically replicating negative-stranded RNA viruses (NSVs) that share commonalties in their replication cycles, such as replication in cytoplasmic inclusion bodies [10,[21][22][23][24]. Importantly, we also could show that NXF1 is important for the life cycle of EBOV in context of infectious virus [19].…”
Section: Introductionmentioning
confidence: 74%
“…A second challenge during the EBOV life cycle is the fact that viral RNA synthesis occurs in inclusion bodies. These are increasingly appreciated for their importance in the genome replication of cytoplasmically replicating NSVs [12,[21][22][23]51], and have for some of these viruses been described to show properties of liquid organelles [24,52]. Similar properties have been observed for EBOV inclusion bodies [10], suggesting that inclusion bodies of NSVs might generally represent liquid organelles.…”
Section: A Model For the Function Of Nxf1 In The Ebov Life Cyclementioning
confidence: 80%